2019
DOI: 10.3389/fnins.2019.00421
|View full text |Cite
|
Sign up to set email alerts
|

In vivo Two-Photon Imaging of Anesthesia-Specific Alterations in Microglial Surveillance and Photodamage-Directed Motility in Mouse Cortex

Abstract: Two-photon imaging of fluorescently labeled microglia in vivo provides a direct approach to measure motility of microglial processes as a readout of microglial function that is crucial in the context of neurodegenerative diseases, as well as to understand the neuroinflammatory response to implanted substrates and brain-computer interfaces. In this longitudinal study, we quantified surveilling and photodamage-directed microglial processes motility in both acute and chronic cranial window … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(34 citation statements)
references
References 51 publications
0
32
2
Order By: Relevance
“…Our results are thus in line with previous studies showing that blocking NMDAR-mediated glutamatergic transmission induced a significant decrease in microglial motility in retinal explants (−12.5% decrease) while GABA application decreased microglial motility as well (−7.9% decrease) [ 35 ]. However, the reduction that we observed with ketamine/xylazine does not match a recent study that reports no effect of ketamine/xylazine anesthesia on microglial motility [ 13 ]. Even though both studies were performed in vivo , several discrepancies should be highlighted: 1) we used a thin-skull cranial preparation, which is more immunologically inert compared to cranial window preparation used by this study; 2) Sun et al .…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Our results are thus in line with previous studies showing that blocking NMDAR-mediated glutamatergic transmission induced a significant decrease in microglial motility in retinal explants (−12.5% decrease) while GABA application decreased microglial motility as well (−7.9% decrease) [ 35 ]. However, the reduction that we observed with ketamine/xylazine does not match a recent study that reports no effect of ketamine/xylazine anesthesia on microglial motility [ 13 ]. Even though both studies were performed in vivo , several discrepancies should be highlighted: 1) we used a thin-skull cranial preparation, which is more immunologically inert compared to cranial window preparation used by this study; 2) Sun et al .…”
Section: Discussioncontrasting
confidence: 99%
“…Isoflurane effects have been largely studied on microglial cells in situ and in vivo , but no consensus has been reached with regards to its effect on microglial morphodynamics [ 5 , 12 , 13 ]. Ketamine/xylazine and urethane were found to increase microglial process area and process surveillance territory [ 5 ], but this was not corroborated by other studies [ 12 , 13 ]. These discrepancies between studies may account for different preparations and/or microglial states.…”
Section: Introductionmentioning
confidence: 99%
“…To track microglial turnover in vivo under basal conditions, we imaged microglia daily in the same awake young adult mice using the microglial-labeled CX3Cr1 GFP/+ transgenic mouse line (Jung et al, 2000) and a chronic cranial window preparation. Because a growing body of literature suggests that microglia behave differently under anesthesia (Li et al, 2012;Stowell et al, 2019;Sun et al, 2019) we wanted to capture the dynamics of microglia in the absence of anesthesia to avoid potentially inducing long-term alteration in microglial movement and turnover during repopulation. Microglia in the same cortical area could easily be imaged and tracked from day to day (Figure 1a and Supplementary video 1) without overt changes in microglial morphology which could indicate immune activation over time.…”
Section: Resultsmentioning
confidence: 99%
“…(Liu et al, 2019;Stowell et al, 2019;Sun et al, 2019), allowing us to reliably track microglial process extension and retraction on the order of minutes(Figure 6a-c). PLX treatment led to only a modest decrease in motility…”
mentioning
confidence: 99%
“…Microglia have been realized to play an important role in neuronal diseases in the studies conducted to better understand the damage occurring in the CNS. Although time-interval morphological examinations were carried out in the early days, the detection of inactive microglia in neurocortex in in vivo studies with the development of two-photon imaging techniques was an important turning point (Sun et al, 2019). The stages of transition from inactive to active form were determined in ongoing studies, and the cell was observed to withdraw the branches of branched bodies in this process (Figure 1).…”
Section: Morphology and Physiology Of Microgliamentioning
confidence: 99%